A Long and Twisted Road: The Journey from EAD to ArchivesSpace Implementation at the University of Minnesota. Issue 3 (1st October 2016) - Dietrick, Kate; Friedman-Shedlov, Lara; Marineau, Caitlin
ABSTRACT: This article will provide an overview of the implementation of EAD by the Archives and Special Collections Department, University of Minnesota Libraries, and the decision to implement ArchivesSpace, which necessitated addressing divergent and legacy practices. Some attention will be given to previous efforts to standardize description and accessibility at the University of Minnesota and how those efforts ultimately failed without a centralized content management system.